2008
DOI: 10.1002/anie.200801359
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl Propargylation from the Alcohol or Aldehyde Oxidation Level Employing 1,3‐Enynes as Surrogates to Preformed Allenylmetal Reagents: A Ruthenium‐Catalyzed CC Bond‐Forming Transfer Hydrogenation

Abstract: Over the past half century, numerous protocols for carbonyl propargylation using allenylmetal reagents have been developed.[1] Allenic Grignard reagents were used by Prévost et al.[2a] in carbonyl additions to furnish mixtures of β-acetylenic and α-allenic carbinols, which led to them to coin the term "propargylic transposition." [2a,b] Subsequent studies by Chodkiewicz and co-workers[2c] demonstrated relative stereocontrol in such additions. Shortly thereafter, Lequam and Guillerm[2d] reported that isolabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…Despite this unfavorable precedent, enyne-alcohol transfer hydrogenative coupling delivers the desired products of carbonyl propargylation as single regioisomers using a catalyst prepared in situ from RuHCl(CO)(PPh 3 ) 3 and DPPF. [38] Iridium complexes also catalyze this process, but ruthenium catalysts were found to be superior.…”
Section: Hydrogenative Carbonyl Propargylation Employing 13-enynes Amentioning
confidence: 99%
“…Despite this unfavorable precedent, enyne-alcohol transfer hydrogenative coupling delivers the desired products of carbonyl propargylation as single regioisomers using a catalyst prepared in situ from RuHCl(CO)(PPh 3 ) 3 and DPPF. [38] Iridium complexes also catalyze this process, but ruthenium catalysts were found to be superior.…”
Section: Hydrogenative Carbonyl Propargylation Employing 13-enynes Amentioning
confidence: 99%
“…In contrast, completely atom-economical carbonyl propargylation is achieved upon ruthenium-catalyzed transfer hydrogenation of 1,3-enynes in the presence of benzylic, allylic, and aliphatic alcohols. Here, hydrogen transfer from the primary alcohol to the 1,3-enyne generates aldehyde-allenylruthenium pairs, which combine to form products of carbonyl propargylation directly from the alcohol oxidation level [31] (Scheme 9). Identical propargylation products are achieved through enyne-aldehyde coupling in the presence of isopropyl alcohol as the terminal reductant.…”
Section: Resultsmentioning
confidence: 99%
“…[61][62][63] Initially developed conditions provided products of α-methyl-propargylation as diastereomeric mixtures. 61 Identical products of propargylation are generated upon 2-propanol mediated 1,3-enyne-aldehyde reductive coupling. 62 In subsequent work, it was found that antidiastereoselectivity improves upon use of sterically demanding reactants.…”
Section: Conversion Of Primary Alcohols To Secondary Alcoholsmentioning
confidence: 99%